Method for preparing super-hydrophilic antireflection coating through phase separation

Through the phase separation process of organic polymer, silica, and titanium dioxide composite sol, a porous anti-reflection coating is formed, which solves the problems of poor moisture resistance and high cost, and achieves efficient anti-reflection effect and improved moisture resistance.

CN119263648APending Publication Date: 2025-01-07BEIJING INST OF FUTURE SCI & TECH ON BIOINSPIRED INTERFACE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393567.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing anti-reflection coatings have poor humidity resistance, high cost and limited anti-reflection effect, making it difficult to maintain performance in high humidity environments.

Method used

The composite sol is composed of organic polymers, silica, titanium dioxide, etc., and the inorganic sol and organic polymer are induced to form nanoscale templates under appropriate sol composition and ambient temperature and humidity through the phase separation process to obtain a porous anti-reflective coating. Avoid pore blockage, improve moisture resistance and cost-effectiveness.

Benefits of technology

A super hydrophilic anti-reflection coating with good humidity resistance and low cost is achieved, which significantly improves the anti-reflection effect, avoids performance degradation caused by pore blockage, and enhances performance in high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263648A_ABST
    Figure CN119263648A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a super-hydrophilic anti-reflection coating through phase separation, which comprises the following steps of: forming composite sol by using an organic polymer, silicon dioxide, titanium dioxide and the like, and inducing phase separation of inorganic sol and the organic polymer along with solvent evaporation in a film forming process of the composite sol. Under proper sol composition, ambient temperature and humidity, the organic polymer can be controlled to form a nanoscale template, and finally the template is removed to obtain the porous antireflection self-cleaning coating. The whole process does not need hard polymer templates such as polystyrene spheres, the relative cost is lower, and the preparation process is simple. According to the method, the polymer template is subjected to accurate control phase separation, and the super-hydrophilic antireflection coating with larger aperture and better effect is obtained. The anti-reflection coating with a larger pore structure is obtained, the effect of the anti-reflection coating in a high-humidity environment can be improved, and the problems that the performance of the anti-reflection coating is reduced due to pore blockage and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical technology, and in particular to a method for preparing a super-hydrophilic anti-reflection coating by phase separation. Background Art

[0002] Anti-reflective coatings are widely used in solar cells, glass curtain walls, optical equipment, etc. The refractive index of ordinary glass is about 1.51, and about 8% of the reflected light is reflected. If the refractive index is reduced to below 1.3, this part of the reflected light can be eliminated, avoiding glare on the glass surface and increasing light transmission.

[0003] There are various methods for preparing anti-reflection coatings. For example, the traditional use of low-refractive index material magnesium fluoride can achieve anti-reflection effect, but the corresponding material is relatively expensive, and a more complex atomic layer deposition or magnetron sputtering method is required to construct a uniform coating on the surface. In addition, the refractive index of magnesium fluoride is 1.38, which is still relatively high, making the anti-reflection effect limited. Porous coatings will further reduce the overall refractive index of the coating due to the presence of pores, and are widely used to construct anti-reflection coatings. For example, strategies such as hollow nanospheres, polymer surfactant templates, and stacking of silica spheres are used to prepare porous anti-reflection coatings; in addition, the presence of nanoporous structures is conducive to improving hydrophilicity, and anti-reflection coatings with super-hydrophilic properties can avoid fogging on the surface of optical materials and better meet some practical application requirements. However, surfactants as templates face the problems of small pore size and insufficient weather resistance; polystyrene spheres as templates are expensive; the synthesis of hollow nanospheres themselves is relatively complex, and the cost of preparing anti-reflection coatings is high, and the uniformity of the coating is general.

[0004] Therefore, there is a need for an anti-reflection coating with good moisture resistance, low cost and significant anti-reflection effect. Summary of the invention

[0005] The present invention is to solve the problems of poor moisture resistance, high cost and unimproved anti-reflection effect of anti-reflection coatings, and provides a method for preparing super-hydrophilic anti-reflection coatings by phase separation, using organic polymers, silicon dioxide, titanium dioxide and the like to form a composite sol, and during the film-forming process, as the solvent evaporates, the composite sol can induce phase separation between inorganic sol and organic polymer. Under suitable sol composition and ambient temperature and humidity, the organic polymer can be controlled to form a nanoscale template, and finally the template is removed to obtain a porous anti-reflection self-cleaning coating. The whole process does not require hard polymer templates such as polystyrene beads, which is relatively lower in cost and simple in preparation process. The present invention precisely controls the phase separation of the polymer template to obtain an anti-reflection coating with a larger pore size, better effect and super-hydrophilicity. The present invention obtains an anti-reflection coating with a larger pore structure, which can improve the effect of the anti-reflection coating in a high humidity environment and avoid the problem of performance degradation of the anti-reflection coating due to pore blockage.

[0006] The present invention provides a method for preparing a super-hydrophilic anti-reflection coating by phase separation, comprising the following steps:

[0007] S1. preparing an inorganic sol, wherein the inorganic sol is: a silica sol or a titania sol or a silica / titania mixed sol;

[0008] The inorganic sol and the organic polymer are uniformly mixed and diluted with anhydrous ethanol to obtain a composite sol, wherein the solid content of the composite sol is 1-8%, the inorganic sol content is 1-10%, the organic polymer is soluble in anhydrous ethanol aqueous solution, and the thermal decomposition temperature of the organic polymer is lower than the thermal decomposition temperature of silicon dioxide and titanium dioxide and lower than 550° C.;

[0009] S2, washing and drying the substrate, coating the composite sol on the surface of the substrate by spraying, pulling, dripping or roller coating, and curing to obtain a substrate with a coating, wherein the organic polymer serves as a polymer template of the inorganic sol in the coating;

[0010] S3. The coated substrate is placed in a muffle furnace and calcined at a temperature of 300 to 600°C for 0.5 to 2 hours. The organic polymer is completely thermally decomposed, and the polymer template and silica sol or titania sol or silica / titania sol are subjected to evaporation-induced phase separation to obtain a super-hydrophilic anti-reflection coating. A method for preparing a super-hydrophilic anti-reflection coating by phase separation is completed.

[0011] The method for preparing a super-hydrophilic anti-reflective coating by phase separation described in the present invention is, as a preferred embodiment, in step S1, the organic polymer includes one or more of the following: polyacrylamide, polyvinyl alcohol, polyvinyl acetate, polyethylene imine, polymaleic acid, polyethylene glycol, tannic acid, polystyrene sulfonic acid, polylactic acid, polyacrylic acid, polymethacrylic acid, polyvinyl butyral and ethyl cellulose.

[0012] The method for preparing a super-hydrophilic anti-reflective coating by phase separation of the present invention is, as a preferred embodiment, in step S1, the preparation method of the silica sol is: using tetraethyl silicate, nitric acid, deionized water and anhydrous ethanol as raw materials for preparation, and the molar ratio of tetraethyl silicate, nitric acid, deionized water and anhydrous ethanol is 1:0.005-0.1:3-10:5-20;

[0013] First, tetraethyl silicate and half volume of anhydrous ethanol are mixed evenly to obtain a mixture of tetraethyl silicate and anhydrous ethanol; after stirring under magnetic force for 20 minutes, nitric acid, deionized water and the other half volume of anhydrous ethanol are mixed evenly, added dropwise into the mixture of tetraethyl silicate and anhydrous ethanol at room temperature, and then stirred continuously in a sealed glass bottle for 6 hours to obtain a silica sol, which is then mixed with an organic polymer after aging.

[0014] In the method for preparing a super-hydrophilic anti-reflection coating by phase separation described in the present invention, as a preferred mode, the aging method of the silica sol is: aging at 60° C. for 1 to 7 days.

[0015] The method for preparing a super-hydrophilic anti-reflective coating by phase separation of the present invention is, as a preferred embodiment, in step S1, the method for preparing the titanium dioxide sol is: using isopropyl titanate, nitric acid, deionized water, anhydrous ethanol and a stabilizer as raw materials, and the molar ratio of isopropyl titanate, nitric acid, deionized water and anhydrous ethanol in the raw materials is 1:0.005-0.1:3-10:5-50;

[0016] First, isopropyl titanate and half volume of anhydrous ethanol are mixed evenly, and then 0.2 molar ratio of a stabilizer is added to obtain an isopropyl titanate solution. After stirring under magnetic force for 20 minutes, nitric acid, deionized water and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the isopropyl titanate solution at room temperature. After continuous stirring for 6 hours in a sealed glass bottle, a titanium dioxide sol is obtained. After aging, the titanium dioxide sol is mixed with an organic polymer.

[0017] In the method for preparing a super-hydrophilic anti-reflective coating by phase separation described in the present invention, as a preferred embodiment, the stabilizer is acetylacetone;

[0018] The aging method of the titanium dioxide sol is aging at 60° C. for 1 to 7 days.

[0019] In the method for preparing a super-hydrophilic anti-reflective coating by phase separation described in the present invention, as a preferred embodiment, the silica / titania mixed sol is obtained by mixing aged silica sol and aged titania sol in any proportion.

[0020] The method for preparing a super-hydrophilic anti-reflection coating by phase separation described in the present invention is, as a preferred mode, when the inorganic sol includes titanium dioxide, the super-hydrophilic anti-reflection coating can be self-cleaning.

[0021] In the method for preparing a super-hydrophilic anti-reflective coating by phase separation described in the present invention, as a preferred embodiment, in step S1, the inorganic sol may also be a metal oxide sol;

[0022] In step S2, the substrate is any one of the following: glass, metal, fiber cloth and plastic;

[0023] In step S3, the polymer template is removed by solvent immersion or plasma etching, and the solvent includes anhydrous ethanol, ethyl acetate, n-hexane and water.

[0024] The method for preparing a super-hydrophilic anti-reflective coating by phase separation of the present invention is preferably as follows: in step S1, the inorganic sol and the organic polymer are uniformly mixed by stirring for 2 hours;

[0025] In step S2, the curing time is more than 16 hours, the temperature is room temperature, and the ambient humidity is 30-60%;

[0026] In step S3, the super-hydrophilic anti-reflection coating is a nanoporous structure, the light transmittance of the super-hydrophilic anti-reflection coating is greater than 94%, the average light transmittance of 400-800nm ​​wavelength is greater than 96%, the contact angle is less than 5°, and the porosity is 40-60%.

[0027] The present invention uses a polymer template to directly phase separate to construct an anti-reflection coating, and the obtained porous anti-reflection coating has the advantages of good moisture resistance, low cost, and significant anti-reflection effect. The anti-reflection coating is prepared by the principle of evaporation-induced phase separation, and the polymer can be phase-separated from the sol to obtain a porous coating; when the inorganic sol contains titanium dioxide, it can also have a photocatalytic self-cleaning effect.

[0028] The preparation of anti-reflective coating mainly includes three steps: preparation of organic-inorganic composite sol, coating film formation, and template removal.

[0029] (1) Preparation of organic-inorganic composite sol

[0030] The organic-inorganic composite sol is composed of a mixture of an organic polymer and an inorganic sol. In order to form a uniform solution with the inorganic sol, the selected organic polymer is a polymer soluble in an anhydrous ethanol aqueous solution. While ensuring the formation of a uniform solution, phase separation and aggregation can occur after the solvent evaporates. The organic polymer used includes one or more mixed compositions of polyacrylamide, polyvinyl alcohol, polyvinyl acetate, polyethyleneimine, polymaleic acid, polyethylene glycol, tannic acid, polystyrene sulfonic acid, polylactic acid, polyacrylic acid, polymethacrylic acid, polyvinyl butyral, ethyl cellulose, etc. Soluble inorganic sols in alcohol aqueous solution include silicon dioxide sol, titanium dioxide sol and mixed sols thereof. The prepared organic-inorganic composite sol is transparent, and precipitation and gelation will not occur when placed for a long time for one month at room temperature.

[0031] Silica sol is prepared by the following steps. Tetraethyl silicate (TEOS), HNO3, deionized water and anhydrous ethanol are used as raw materials. The solution is prepared according to the ratio of TEOS:HNO3:H2O:EtOH=1:0.005~0.1:3~10:5~20. First, TEOS and half volume of anhydrous ethanol raw material are mixed evenly, stirred under magnetic force for 20 minutes, and then HNO3, H2O and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the mixture of TEOS and anhydrous ethanol at room temperature, and the silica sol is obtained after continuous stirring in a sealed glass bottle for 6 hours. After the sol is aged at 60°C for 1 to 7 days, the desired silica sol is obtained.

[0032] Titanium dioxide sol is prepared by the following steps. Titanium isopropyl titanate (TIPT), HNO3, deionized water, anhydrous ethanol, and acetylacetone are used as raw materials. The solution is prepared according to the molar ratio of TIPT:HNO3:H2O:EtOH=1:0.005~0.1:3~10:5~50. First, TIPT and half the volume of anhydrous ethanol raw material are mixed evenly, and 0.2 molar ratio of acetylacetone is added as a stabilizer, and stirred under magnetic force for 20 minutes. Then, HNO3, H2O and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the TIPT solution at room temperature. Titanium dioxide sol is obtained after continuous stirring in a sealed glass bottle for 6 hours. After the sol is aged at 60°C for 1 to 7 days, the desired titanium dioxide sol is obtained. The titanium dioxide sol is a light yellow uniform transparent sol, which can be mixed with silica sol in any proportion to obtain a silica and titanium dioxide composite sol.

[0033] The obtained inorganic sol and organic polymer are continuously stirred for 2 hours, and are fully mixed to obtain an organic-inorganic composite sol, which is diluted with anhydrous ethanol. The polymer solid content in the obtained composite sol is controlled to be 1-8%, and the inorganic sol solid content is controlled to be 1-10%.

[0034] (2) Coating film forming process

[0035] Before coating, the glass surface is cleaned with water and anhydrous ethanol for several times and dried at room temperature. The obtained organic-inorganic composite sol is directly formed on the material surface by spraying, pulling, dripping, roller coating and other methods, and cured at room temperature for 24 hours. The film forming temperature is room temperature and the ambient humidity is 30-60%.

[0036] (3) Removal of polymer template

[0037] The coated glass is placed in a muffle furnace, the calcination temperature is controlled to be 300-600° C., the calcination time is 0.5-2 hours, the polymer template is completely removed, and a porous anti-reflection coating is obtained.

[0038] The inorganic sol in the organic-inorganic composite sol of the present invention is not limited to silicon dioxide and titanium dioxide sols, and other metal oxide sols such as zirconium dioxide, aluminum oxide, etc. are also applicable.

[0039] The substrate material applicable to the present invention is not limited to glass, and other various substrates such as metal, fiber cloth, plastic, etc. are also included.

[0040] The method for removing the polymer template of the present invention is not limited to high-temperature calcination. The coating prepared by this method is also applicable to other methods such as solvent immersion (anhydrous ethanol, ethyl acetate, n-hexane, water, etc.) and plasma etching to remove the polymer template to obtain an anti-reflective coating.

[0041] The present invention uses organic polymer, silicon dioxide, titanium dioxide and the like to form a composite sol. During the film-forming process of the composite sol, as the solvent evaporates, the entire sol system is no longer stable, inducing the inorganic sol and the organic polymer to separate into phases, and the inorganic sol undergoes a condensation reaction to form a single phase, and the organic polymer forms another phase; in order to obtain a nanoscale porous coating, the present invention reasonably regulates the sol composition, ambient temperature and humidity, so that the degree of aggregation of the organic polymer after phase separation is at the nanoscale (<~100nm), avoiding the final coating having large pores, causing light scattering and affecting the anti-reflection effect; finally, the template is removed to obtain a porous anti-reflection self-cleaning coating, and the porous structure comes from the pores left after the organic polymer template is removed. Since the template is removed by calcining the polymer, not only a porous structure is generated, but also a large number of hydroxyls are formed on the coating surface, so that the final coating has super-hydrophilicity. The whole process does not require hard polymer templates such as polystyrene beads, and the relative cost is lower and the preparation process is simple.

[0042] The present invention has the following advantages:

[0043] The present invention uses an evaporation-induced phase separation method to prepare a porous super-hydrophilic SiO2 coating with anti-reflection, and the anti-reflection performance has obvious advantages. Compared with the existing methods such as polymer surfactants to prepare anti-reflection coatings, the whole process of the present invention does not require hard polymer templates such as polystyrene beads, and the cost is relatively lower and the preparation process is simple; the present invention can obtain an anti-reflection coating with a larger pore structure, improve the effect of the anti-reflection coating in a high humidity environment, and avoid the problem of performance degradation of the anti-reflection coating due to pore blockage. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A diagram of a method for preparing a super-hydrophilic anti-reflection coating by phase separation;

[0045] Figure 2 A schematic diagram of the process of generating silica sol for preparing super hydrophilic anti-reflection coating by phase separation;

[0046] Figure 3 A schematic diagram of the titanium dioxide sol generation process for preparing a super-hydrophilic anti-reflection coating by phase separation;

[0047] Figure 4 The light transmittance curves of ordinary glass and anti-reflection glass in Example 1 of preparing a super-hydrophilic anti-reflection coating by phase separation;

[0048] Figure 5 This is a contact angle test picture of the coating of Example 1 of a super-hydrophilic anti-reflection coating prepared by phase separation;

[0049] Figure 6 This is a scanning electron microscope top view of the coating of Example 1 of a super-hydrophilic anti-reflective coating prepared by phase separation, with a scale of 500 nm;

[0050] Figure 7 The light transmittance curves of ordinary glass and anti-reflection glass in Example 2 of preparing a super-hydrophilic anti-reflection coating by phase separation;

[0051] Figure 8 This is a transmittance curve of ordinary glass and anti-reflection glass in Example 3 of preparing a super-hydrophilic anti-reflection coating by phase separation. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0053] Example 1

[0054] like Figure 1 A method for preparing a super-hydrophilic anti-reflection coating by phase separation comprises the following steps:

[0055] (1) Preparation of organic-inorganic composite sol

[0056] like Figure 2 As shown, silica sol is prepared by the following steps. Tetraethyl silicate (TEOS), HNO3, deionized water, and anhydrous ethanol are used as raw materials. The solution is prepared according to the ratio of TEOS:HNO3:H2O:EtOH=1:0.05:4:10. First, TEOS and half the volume of anhydrous ethanol raw materials are mixed evenly, stirred under magnetic force for 20 minutes, and then HNO3, H2O and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the mixture of TEOS and anhydrous ethanol at room temperature, and the silica sol is obtained after continuous stirring in a sealed glass bottle for 6 hours. After the sol is aged at 60°C for 1 day, the desired silica sol is obtained.

[0057] The obtained inorganic sol and tannic acid were stirred continuously for 2 hours and fully mixed to obtain an organic-inorganic composite sol, which was diluted with anhydrous ethanol so that the polymer solid content in the composite sol was controlled to be 2% and the inorganic sol solid content was controlled to be 3%.

[0058] (2) Coating film forming process

[0059] Before coating, the glass surface was cleaned with water and anhydrous ethanol several times and dried at room temperature. The obtained organic-inorganic composite sol was directly formed into a film on the material surface by pulling, and the pulling speed was controlled to be 2mm / s. Then the sample was cured at room temperature for 24h. The film forming temperature was room temperature and the ambient humidity was 40-50%.

[0060] (3) Removal of polymer template

[0061] The coated glass was placed in a muffle furnace, the calcination temperature was controlled to be 550° C., the calcination time was 1 hour, the polymer template was completely removed, and a porous anti-reflection coating was obtained.

[0062] (4) Implementation Effect

[0063] like Figure 4 As shown, the light transmittance of the anti-reflection glass with coating can reach up to 99.2%, and the average light transmittance of 400-800nm ​​wavelength is 97.5%, which is 7.1% higher than that of ordinary glass, and the contact angle is less than 5°( Figure 5 ). Figure 6 Scanning electron microscopy images show that the coating surface has a nanoporous structure with a porosity of ~60%.

[0064] Example 2

[0065] like Figure 1 A method for preparing a super-hydrophilic anti-reflection coating by phase separation comprises the following steps:

[0066] (1) Preparation of organic-inorganic composite sol

[0067] like Figure 3As shown, the titanium dioxide sol is prepared by the following steps: using isopropyl titanate (TIPT), HNO3, deionized water, anhydrous ethanol, and acetylacetone as raw materials. The solution is prepared according to the molar ratio of TIPT:HNO3:H2O:EtOH=1:0.01:4:40. First, TIPT and half the volume of anhydrous ethanol raw materials are mixed evenly, and 0.2 molar ratio of acetylacetone is added as a stabilizer, and stirred under magnetic force for 20 minutes, and then HNO3, H2O and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the TIPT solution at room temperature, and the titanium dioxide sol is obtained after continuous stirring in a sealed glass bottle for 6 hours. After the sol is aged at 60°C for 3 days, the desired titanium dioxide sol is obtained, and the titanium dioxide sol is a light yellow uniform transparent sol.

[0068] The obtained titanium dioxide sol and polyvinyl butyral were stirred continuously for 2 hours and fully mixed to obtain an organic-inorganic composite sol, which was diluted with anhydrous ethanol to control the polymer solid content in the composite sol to 1.2% and the inorganic sol solid content to 1.2%.

[0069] (2) Coating film forming process

[0070] Before coating, the glass surface is cleaned with water and anhydrous ethanol for several times and dried at room temperature. The obtained organic-inorganic composite sol is directly formed into a film on the material surface by spraying and cured at room temperature for 24 hours. The film forming temperature is room temperature and the ambient humidity is 40-50%.

[0071] (3) Removal of polymer template

[0072] The glass with coating on one side is placed in a muffle furnace, the calcination temperature is controlled to be 400° C., the calcination time is 1 hour, the polymer template is completely removed, and a porous anti-reflection coating is obtained.

[0073] (4) Implementation Effect

[0074] like Figure 7 As shown in the figure, on glass, the light transmittance of the single-sided sprayed anti-reflection glass can reach up to 94.5%, the contact angle is less than 5°, and the porosity is 50%.

[0075] Example 3

[0076] like Figure 1 A method for preparing a super-hydrophilic anti-reflection coating by phase separation comprises the following steps:

[0077] (1) Preparation of organic-inorganic composite sol

[0078] like Figure 2As shown, silica sol is prepared by the following steps. Tetraethyl silicate (TEOS), HNO3, deionized water, and anhydrous ethanol are used as raw materials. The solution is prepared according to the ratio of TEOS:HNO3:H2O:EtOH=1:0.01:5:10. First, TEOS and half the volume of anhydrous ethanol raw materials are mixed evenly, stirred under magnetic force for 20 minutes, and then HNO3, H2O and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the mixture of TEOS and anhydrous ethanol at room temperature, and the silica sol is obtained after continuous stirring in a sealed glass bottle for 6 hours. After the sol is aged at 60°C for 1 day, the desired silica sol is obtained.

[0079] like Figure 3 As shown, the titanium dioxide sol is prepared by the following steps. Use isopropyl titanate (TIPT), HNO3, deionized water, anhydrous ethanol, and acetylacetone as raw materials. Prepare the solution according to the molar ratio of TIPT:HNO3:H2O:EtOH=1:0.01:4:40. First, TIPT and half the volume of anhydrous ethanol raw material are mixed evenly, and 0.2 molar ratio of acetylacetone is added as a stabilizer, and stirred under magnetic force for 20 minutes. Then, HNO3, H2O and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the TIPT solution at room temperature. After continuous stirring for 6 hours in a sealed glass bottle, the titanium dioxide sol is obtained. After the sol is aged at 60°C for 1 day, the desired titanium dioxide sol is obtained.

[0080] The silica sol and the titanium dioxide sol are mixed to obtain an inorganic sol, wherein the solid content of titanium dioxide accounts for 20% and the solid content of silica accounts for 80%. The inorganic sol and polyacrylic acid are stirred for 2 hours and fully mixed to obtain an organic-inorganic composite sol. The final composite sol is diluted with anhydrous ethanol, and the polymer solid content is controlled to be 2% and the inorganic sol solid content is controlled to be 3%.

[0081] (2) Coating film forming process

[0082] Before coating, the glass surface was cleaned with water and anhydrous ethanol for several times and dried at room temperature. The obtained organic-inorganic composite sol was directly formed into a film on the material surface by pulling, and the pulling speed was controlled to 2mm / s, and then cured at room temperature for 24h. The film forming temperature was room temperature, and the ambient humidity was 40-50%.

[0083] (3) Removal of polymer template

[0084] The coated glass was placed in a muffle furnace, the calcination temperature was controlled to be 450° C., the calcination time was 0.5 hours, the polymer template was completely removed, and a porous anti-reflection coating was obtained.

[0085] (4) Implementation Effect

[0086] like Figure 8 As shown, on the glass, the anti-reflection glass with coating on both sides is obtained by pulling, and the light transmittance can reach up to 98.2%. The average light transmittance of 400-800nm ​​wavelength is 96.7%, which is 6.3% higher than that of ordinary glass, the contact angle is less than 5°, and the porosity is 50%.

[0087] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a super-hydrophilic anti-reflection coating by phase separation, characterized in that: The following steps are involved: S1. preparing an inorganic sol, wherein the inorganic sol is: a silica sol or a titania sol or a silica / titania mixed sol; The inorganic sol and the organic polymer are uniformly mixed and diluted with anhydrous ethanol to obtain a composite sol, wherein the solid content of the composite sol is 1-8%, the inorganic sol content is 1-10%, the organic polymer is soluble in anhydrous ethanol aqueous solution, and the thermal decomposition temperature of the organic polymer is lower than the thermal decomposition temperature of silicon dioxide and titanium dioxide and lower than 550° C.; S2, washing and drying the substrate, coating the composite sol on the surface of the substrate by spraying, pulling, dripping or roller coating, and curing to obtain a substrate with a coating, wherein the organic polymer serves as a polymer template of the inorganic sol in the coating; S3. The coated substrate is placed in a muffle furnace and calcined at a temperature of 300 to 600° C. for 0.5 to 2 hours. The organic polymer is completely thermally decomposed. The polymer template and silica sol or titania sol or silica / titania sol are subjected to evaporation-induced phase separation to obtain a super-hydrophilic anti-reflection coating. A method for preparing a super-hydrophilic anti-reflection coating by phase separation is completed.

2. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 1, characterized in that: In step S1, the organic polymer includes one or more of the following: polyacrylamide, polyvinyl alcohol, polyvinyl acetate, polyethylene imine, polymaleic acid, polyethylene glycol, tannic acid, polystyrene sulfonic acid, polylactic acid, polyacrylic acid, polymethacrylic acid, polyvinyl butyral and ethyl cellulose.

3. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 1, characterized in that: In step S1, the preparation method of the silica sol is: using tetraethyl silicate, nitric acid, deionized water and anhydrous ethanol as raw materials for preparation, and the molar ratio of tetraethyl silicate, nitric acid, deionized water and anhydrous ethanol is 1:0.005-0.1:3-10:5-20; First, tetraethyl silicate and half volume of anhydrous ethanol are mixed evenly to obtain a mixture of tetraethyl silicate and anhydrous ethanol; after stirring under magnetic force for 20 minutes, nitric acid, deionized water and the other half volume of anhydrous ethanol are mixed evenly, added dropwise into the mixture of tetraethyl silicate and anhydrous ethanol at room temperature, and then stirred continuously in a sealed glass bottle for 6 hours to obtain the silica sol, and the silica sol is mixed with the organic polymer after aging.

4. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 3, characterized in that: The aging method of the silica sol is: aging at 60° C. for 1 to 7 days.

5. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 3, characterized in that: In step S1, the preparation method of titanium dioxide sol is: using isopropyl titanate, nitric acid, deionized water, anhydrous ethanol and a stabilizer as raw materials, and the molar ratio of isopropyl titanate, nitric acid, deionized water and anhydrous ethanol in the raw materials is 1:0.005-0.1:3-10:5-50; First, isopropyl titanate and half volume of anhydrous ethanol are mixed evenly, and then 0.2 molar ratio of a stabilizer is added to obtain an isopropyl titanate solution. After stirring under magnetic force for 20 minutes, nitric acid, deionized water and the other half volume of anhydrous ethanol are mixed evenly, and then added dropwise to the isopropyl titanate solution at room temperature. After continuous stirring for 6 hours in a sealed glass bottle, a titanium dioxide sol is obtained. After aging, the titanium dioxide sol is mixed with the organic polymer.

6. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 4, characterized in that: The stabilizer is acetylacetone; The aging method of the titanium dioxide sol is aging at 60° C. for 1 to 7 days.

7. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 5, characterized in that: The silica / titania mixed sol is obtained by mixing the aged silica sol and the aged titania sol in any proportion.

8. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 1, characterized in that: When titanium dioxide is included in the inorganic sol, the super hydrophilic anti-reflection coating can be self-cleaning.

9. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 1, characterized in that: In step S1, the inorganic sol may also be a metal oxide sol; In step S2, the substrate is any one of the following: glass, metal, fiber cloth and plastic; In step S3, the polymer template is removed by solvent immersion or plasma etching, and the solvent includes anhydrous ethanol, ethyl acetate, n-hexane and water.

10. The method for preparing a super-hydrophilic anti-reflection coating by phase separation according to claim 1, characterized in that: In step S1, the inorganic sol and the organic polymer are mixed uniformly by stirring for 2 hours; In step S2, the curing time is more than 16 hours, the temperature is room temperature, and the ambient humidity is 30-60%; In step S3, the super-hydrophilic anti-reflection coating is a nanoporous structure, the light transmittance of the super-hydrophilic anti-reflection coating is greater than 94%, the average light transmittance at a wavelength of 400-800 nm is greater than 96%, the contact angle is less than 5°, and the porosity is 40-60%.